Pengaruh Penerapan Aplikasi Electronic Filing (E-Filing) Dan Pemahaman Internet Terhadap Kepatuhan Wajib Pajak Orang Pribadi Bagi Dosen Dan Karyawan Pada Universitas Katolik Widya Mandira Kupang - Maria Goreti Malut; Kornelius Kelemur Kroo; Anggraeny Paridy (Journal on Education, 2023)
Taxpayer compliance can be seen from how to fulfill tax obligations, namely by registering as a taxpayer, compliance in paying and paying tax owed and compliance in reporting and paying arrears. To increase taxpayer compliance, the Directorate General of Taxes seeks to optimize services by utilizing information and communication technology, namely by implementing an electronic filing or e-filing system. This study aims to determine the effect of the application of e-filing and internet understanding on individual taxpayer compliance for lecturers and staff at Widya Mandira Catholic University, Kupang. The method used is to distribute questionnaires through the Google form to lecturers and staff, with a total of 100 respondents. The results showed that the implementation of the e-filing application had no significant effect on individual taxpayer compliance at Widya Mandira Catholic University Kupang as seen from tcount < ttable with a significance value of 0.267 > 0.05. Furthermore, internet comprehension has a significant effect on taxpayer compliance as evidenced by tcount > ttable or 2.123 > 1.985 with a significance value of 0.036 <0.05.